The Evolution of Structural and Communicative Traditions of Policy Analysis in Contemporary Social Science - Barmatova, Svetlana (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The article is devoted to the theoretical synthesis of results of evolution of structural and communicative traditions of analysis of politics that takes place in modern sociological science. Development and fixing of spatial subjects (the topology) within the limits of communicative tradition and heuristic potential of the spatial aaproach to the analysis of politics are analyzed